Sosialisasi Beasiswa dan Pelatihan Penulisan Essay Akademik - Rachman, Sidrah; Nur Fadillah Amir (Jurnal Abdi Masyarakat Pendidikan, 2025)
Access to information about study opportunities abroad, including scholarships and application requirements, is still uneven, especially in the regencies of South Sulawesi. This situation has resulted in a lack of preparedness among prospective applicants and a low number of international scholarship recipients from the region. Therefore, community service activities in the form of Fulbright scholarship socialization and academic essay writing workshops were held to provide information to students and the general public about opportunities to continue their studies. This activity also aimed to equip participants with the skills to write study objectives and personal statements, which are among the application requirements. The activity involved 116 participants who registered online and onsite, with a series of events including an opening ceremony, scholarship information presentation, and essay writing workshop. The results of this activity showed that participants were enthusiastic and actively responded by asking questions during each information session and providing answers when filling out the post-event feedback form. A total of 70% of participants stated that this activity was very good and provided useful information about further study scholarships and academic essay writing as one of the scholarship requirements.